Merdeka Belajar: Upaya Peningkatan Mutu Pembelajaran di Sekolah/Madrasah - Rahmansyah, Muhammad Fahmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
AbstractDuring the 4.0 revolution, education was required to apply new innovations and be able to compete with other educational institutions. To realize Human Resources (HR) that can advance, enhance and realize the ideals of the nation, institutions must be flexible in organizing and providing the latest learning system in the 4.0 revolution era amidst the conditions of the Covid-19 pandemic, with the concept of independent learning which was initiated by the Minister of Education and Culture. Is expected to be able to realize quality learning and be able to compete in the current development of globalization. The design of independent learning, the leadership of the principal is very meaningful, especially in fostering teachers in delivering material, not free from the concept of an independent learning curriculum which was formed in such a way during the Covid 19 period, so that the learning system accelerates concepts and curriculum development programs that are very fast, so that educational innovation realized in the learning experience is needed by students.Keyword: Freedom of Learning, Curriculum, Quality